Worlds of Reference. Lexicography, Learning and Language from the Clay Tablet to the Computer - McArthur, Tom (1986)
19-46: The Ancient World. Sumerisch-babylonische Lexikographie; p. 27 Photo von BM 24964; p. 33 Photos lexikalischer Texte.